(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The traditional system of medicine is so ingrained in our culture that, about 75% of the Indian population depends on this indigenous system for relief. With such a huge section of an ever increasing population relying on herbal remedies, it is imperative that the plant products which have been in use for such a long time be scientifically supported for their efficacy. Diabetes a metabolic disorders is most frequent occurring disease in India. The present paper reports with the investigation of antidiabetic potential of Eugenia jambolana (Bark), Phyllanthus niruri (Whole plant), Momordica charantia Linn. (Seeds) and Nyctanthes arbor-tristis (Leaves).